Techniques for managing projects risk in capital budgeting process - Goran Karanovic; Suzana Baresa; Sinisa Bogdan (UTMS Journal of Economics, 2010)
The paper examines capital budgeting process and techniques of risk analysis in the process of selecting optimal project. Corporate manager in process of capital budgeting uses numerous techniques some of them are based on intuition and experience of manager, and some of them are analytic based on sensitive, scenario, decision tree and Monte Carlo method. All methods are used to determinate and to predict risk influence on the projects. Article deals with analytical techniques and real problems that can arise in capital budgeting process. Trough case study in article we analyzed risks that may emerge from different techniques. Conclusion that emerges from analyzing different methods of risk techniques is that only with right combination of these techniques corporate manager could decide correctly to choose optimal capital project.
Keywords: 330; Monte Carlo; sensitive method; scenario method; decision tree; NPV; discount rate